Analisis Pengaruh BUMDES Terhadap Pengembangan Ekonomi Desa di Era Pasca Pandemic - Munasiron Miftah; Alfatih S. Manggabarani; Marlina Marlina (ITB AAS INDONESIA, 2023)
The existence of Village-Owned Enterprises (BUMDES) as Strengthening the Village Economy. This village-owned enterprise is one of the institutions engaged in the social and economic fields and as a service provider to the village community mainly regarding the field of business. The research method used in this study is a qualitative research with a descriptive approach, with a focus on research: (1) Management Management of Village-Owned Enterprises (2) Community Income Before and After the Existence of Village-Owned Enterprises (BUMDES) in the Post-Pandemic Era. The result of this study is that the existence of village-owned enterprises is in accordance with the regional regulations of Lebak Banten Regency which is then regulated by the village with village regulations regarding village-owned enterprises.) – 8,215. Because probability (Sig) 0.000 < 0.05 then Ho is Rejected, meaning that there is an influence before and after the existence of BUMDes. Based on the results of the processing, it can be concluded that the existence of BUMDes greatly influences the economic development of the village.